2007
DOI: 10.1002/ppul.20582
|View full text |Cite
|
Sign up to set email alerts
|

Physician‐diagnosed asthma and acute chest syndrome: Associations with NOS Polymorphisms

Abstract: The main objectives of this paper were to test the hypothesis that polymorphisms in NOS1 and NOS3 genes associate with ACS in SCD patients and to characterize the association between physician-diagnosed asthma and acute chest syndrome (ACS). Case-control study of sickle cell disease patients >or=5 years old with ACS (cases; n=86) and those without ACS (controls; n=48) was carried out. Associations between ACS and the AAT repeat in intron 13 (formerly intron 20) of the NOS1, and with NOS3 T-786C polymorphism we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…We would need to directly genotype the promoter microsatellite to determine if this SNP captures the association signal with ACS through LD. Similarly, although an intronic sequence repeat polymorphism in the NOS1 gene has been proposed to influence ACS risk, 43,44 none of the NOS1 SNPs tested in our study showed significant association results with ACS.…”
contrasting
confidence: 50%
“…We would need to directly genotype the promoter microsatellite to determine if this SNP captures the association signal with ACS through LD. Similarly, although an intronic sequence repeat polymorphism in the NOS1 gene has been proposed to influence ACS risk, 43,44 none of the NOS1 SNPs tested in our study showed significant association results with ACS.…”
contrasting
confidence: 50%
“…Pulmonary impairment in SCD patients is well described and includes SCCLD, a severe form of chronic lung injury marked by restrictive lung disease and decreased oxygen saturation. 34,[46][47][48][49][50][51][52][53][54] Our patients showed proportional reductions in both FEV 1 and FVC, which implies a restrictive defect with hypoxemia relative to HCs. However, there were negligible changes in FEV 1 , FVC, and SaO 2 in all patient groups after the ingestion of L-arginine at any dose.…”
Section: Discussionmentioning
confidence: 98%
“…Boyd et al 5 reported from the Cooperative Study for Sickle Cell Disease that the frequency of ACS events was twice as high in patients with a diagnosis of asthma. Duckworth et al 6 reported a relationship between physician-diagnosed asthma and ACS. Paul et al 7 in the Pulmonary Hypertension and Hypoxic Response in SCD (PUSH) study found that acute pulmonary events (ACS or pneumonia) were statistically associated with asthma history, frequent pain episodes, abnormal tricuspid regurgitation velocity and WBC.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] The presence of asthma in SCD has been associated with increased risk of developing ACS. In addition, the first ACS event tends to occur at a younger age when compared to patients who do not have asthma.…”
Section: Introductionmentioning
confidence: 99%